The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.5114/aoms.2018.75606
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous regression of asymptomatic walled-off pancreatic necrosis

Abstract: IntroductionAsymptomatic walled-off pancreatic necrosis (WOPN) should be treated conservatively, irrespective of the extent and size of the necrosis. The aim of this study was to evaluate the efficacy and safety of a strategy involving the observation of patients with asymptomatic WOPN over a long period of time.Material and methodsThis study involved the retrospective analysis of 368 patients hospitalized in our department between 2010 and 2016, due to acute pancreatitis and its consequences in the form of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 29 publications
0
11
1
Order By: Relevance
“…The current guidelines on managing ANP recommend postponing endoscopic treatment of necrotic collection by at least 4 weeks since the disease onset 1 , 6 9 , 11 , 15 . In early phase of ANP, it is recommended to intensify conservative treatment with intravenous antibiotics, if necessary 16 , 17 , which can delay or even prevent surgical intervention 6 . However, some patients will still require interventional treatment for ANCs within first 4 weeks of ANP 11 15 , 26 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current guidelines on managing ANP recommend postponing endoscopic treatment of necrotic collection by at least 4 weeks since the disease onset 1 , 6 9 , 11 , 15 . In early phase of ANP, it is recommended to intensify conservative treatment with intravenous antibiotics, if necessary 16 , 17 , which can delay or even prevent surgical intervention 6 . However, some patients will still require interventional treatment for ANCs within first 4 weeks of ANP 11 15 , 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Almost half of all ANCs regresses spontaneously, while the other half tends to evolve into WOPN 4 , 5 . In half of the patients with WOPN, the fluid collection undergoes spontaneous resorption without a need for intervention 4 6 . The other half of the patients develops symptoms related to fluid collection, which is an indication for interventional treatment 4 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Studies on follow-up of asymptomatic patients with WON showed that >50% have either decreased in size or resolution of collection without any intervention [ 9 , 21 ]. In our study, 14 (46.6%) patients had regression of WON size, from 76.57±21 mm to 51.07±21.62 mm during the three-month follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…They are compression symptoms such as obstructive jaundice or ileus [10][11][39][40]. Patients with pancreatic fluid collections without clinical symptoms should not be treated interventionally [10][11]41], because as we have presented in our study, these collections are susceptible to spontaneous regression during the hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…In the last decades we can observe an intensive development of minimally invasive treatment methods of consequences of AP [22][23][24][26][27][38][39][40][41][42][43][44][45]. The application of interventional methods of treatment was presented in our previous publications [38][39][40][41][42]. In the presented sample interventional treatment was needed in 46/202 (22.77%) patients with pancreatic and peripancreatic fluid collections, because of persistent symptoms related with fluid collection.…”
Section: Discussionmentioning
confidence: 99%